Adaptacja libretta operowego na potrzeby realizacji scenicznej – kilka uwag od tłumacza - Agnieszka Muszyńska‑Andrejczyk (Ksiegarnia Akademicka Publishing, 2021)
Adaptation of the operatic libretto to the needs of stage presentation – a few translator’s remarks